Laser cladding powder with high oxygen corrosion resistance and use method thereof
By designing nickel-based alloy powders with appropriate Cr, Ni and other alloying elements, the problem of existing laser cladding powders being difficult to improve the oxygen corrosion resistance of composite pipes in high-oxygen corrosion environments has been solved, and the problem has been achieved in high-oxygen corrosion environments. High corrosion resistance.
Patent Information
- Application Number
- CN202310901436.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-21
AI Technical Summary
It is difficult for existing laser clad powder to effectively improve the oxygen corrosion resistance of composite tubes under high oxygen corrosion environments.
A nickel-based alloy powder containing appropriate Cr, Ni and other alloy elements was designed to improve the oxygen corrosion resistance of the powder through a reasonable component ratio. Specific ingredients include C≤0.03%, Cr: 15~35%, Ni: 30~60%, Mo: 2~5%, Cu: 0.5~3%, Al: 0.1~1.0%, Nb: 0.01~0.1%, The balance is Fe and impurities.
In an oxygen corrosion environment with chloride ions and water, the uniform corrosion rate of the cladding layer prepared by using this powder is ≤0.01mm/y, and the maximum pitting corrosion rate is ≤0.1mm/y, which significantly improves the oxygen corrosion resistance of the composite pipe. performance.
Smart Images

Figure BDA0004351860280000051 
Figure BDA0004351860280000061 
Figure BDA0004351860280000062
Abstract
Description
Technical Field
[0001] The invention relates to an alloy material, in particular to a laser cladding powder. Background Art
[0002] Laser cladding is a process that uses high-energy lasers to rapidly melt powder and the surface of the substrate, and then rapidly solidify the two together to form a thin coating. Laser cladding technology is widely used in the current engineering machinery industry to manufacture composite pipes because of its wide range of material selection, dense coating structure, and little damage to the substrate. In particular, the cladding layer is very thin, which can save a lot of expensive corrosion-resistant alloys. In addition, the laser cladding coating can achieve complete metallurgical bonding with the substrate and has a dense structure.
[0003] The powder used for laser cladding determines the functional characteristics and processing quality of the cladding layer and even the entire composite pipe, so it is particularly important in the laser cladding process.
[0004] The Chinese patent document with the publication number CN108326287A and the publication date of July 27, 2018, entitled "Corrosion-resistant laser cladding powder and its cladding method and use", discloses a laser cladding powder comprising the following powder components by mass fraction: nickel: 9-15%; chromium: 20-30%; molybdenum: 3-5%; boron: 0.5-1%; silicon: 0.5-1%; carbon: 0.1-0.15%; tungsten: 0.7-1.3%; titanium: 0.5-1.6%; nitrogen: 0.2-1.1%: iron: balance. The laser cladding powder forms a corrosion-resistant alloy coating on the surface of the substrate, which can improve the corrosion resistance of ordinary steel, especially the corrosion resistance to high chloride ion environment.
[0005] The Chinese patent document with publication number CN101974724A and publication date February 16, 2011, and titled “Iron-based alloy powder for high-strength and toughness laser cladding coating” discloses an iron-based alloy powder, the components of which are as follows in weight percentage: 0.60% to 1.00% C, 0.35% to 0.70% Si, 0.30% to 0.60% Mn, 5.00% to 7.00% Cr, 2.50% to 4.00% Ni, 1.50% to 2.50% Mo, 1.00% to 1.50% W, 0.70% to 1.00% V, 0.20% to 0.40% Ti, 0.50% to 0.70% B, 0.20% to 0.40% Nb, 0.10% to 0.30% Ce, and the balance is Fe. This invention can obtain a large area of crack-free iron-based laser-clad alloy coating without preheating and post-heat treatment, with a hardness of 62-67HRC and a yield strength of 1700-2000MPa. However, the alloy powder composition is different, mainly to improve the surface hardness and wear resistance of the substrate, but not to solve the corrosion resistance. Summary of the invention
[0006] One of the purposes of the present invention is to provide a laser cladding powder with high oxygen corrosion resistance for manufacturing metallurgical composite pipes. The powder can improve the oxygen corrosion resistance of the composite pipe through reasonable composition design.
[0007] In order to achieve the above object, the present invention provides a laser cladding powder with high oxygen corrosion resistance for manufacturing a metallurgical composite pipe, which contains Fe and inevitable impurities, and also contains the following chemical elements in mass percentage:
[0008] 0<C≤0.03%, Cr: 15~35%, Ni: 30~60%, Mo: 2~5%, Cu: 0.5~3%, Al: 0.1~1.0%, Nb: 0.01~0.1%.
[0009] Accordingly, the present invention also provides a laser cladding powder with high oxygen corrosion resistance for manufacturing a metallurgical composite pipe, wherein the mass percentage of each chemical element is:
[0010] 0<C≤0.03%, Cr: 15~35%, Ni: 30~60%, Mo: 2~5%, Cu: 0.5~3%, Al: 0.1~1.0%, Nb: 0.01~0.1%, and the balance is Fe and inevitable impurities.
[0011] Furthermore, in the laser cladding powder of the present invention, the mass percentage of each chemical element satisfies at least one of the following:
[0012] 0<C≤0.02%;
[0013] Cr: 19-30%;
[0014] Cu: 1-2.5%;
[0015] Al: 0.3-0.8%;
[0016] Nb: 0.03~0.08%.
[0017] The present invention designs a nickel-based alloy powder containing appropriate Cr, Ni and other alloy elements. The composition design idea is: to prepare an alloy powder with excellent corrosion resistance based on the Ni-Cr system, wherein an appropriate amount of Mo element is added to further improve the pitting corrosion resistance of the alloy. Specifically, the design principles of each element are as follows:
[0018] C: In the laser cladding powder of the present invention, C is a strong solid solution strengthening element used to improve the strength of austenitic alloys. However, too high a C content will result in a large amount of M in the austenitic alloy. 23Precipitated phases such as C6, especially at the grain boundaries, are prone to produce chromium-depleted areas, thereby reducing the corrosion resistance of the alloy, especially the intergranular corrosion resistance. Therefore, the C element content in the present invention is controlled to be below 0.03%, and more preferably below 0.02%.
[0019] Cr: In the laser cladding powder of the present invention, Cr is the main element in the alloy that provides corrosion resistance. Generally, when the Cr content of the alloy reaches 15% or more, a continuous, dense, Cr-rich oxide film with excellent protective performance will be formed on the surface of the alloy. As the Cr content increases, the Cr / Fe ratio in the oxide film increases, and the stability and protective performance of the oxide film are better. However, too high Cr in the alloy (>35%) will cause a large amount of σ phase to precipitate, reducing the toughness and plasticity of the material. Therefore, the Cr content in the present invention is controlled at 15-35%, and more preferably at 19-30%.
[0020] Ni: In the laser cladding powder of the present invention, Ni is an element that stabilizes and expands the austenite phase region in the alloy. As the nickel content in the alloy increases, the Ms point decreases, the residual ferrite can be completely eliminated, and the tendency of σ phase formation is significantly reduced. In addition, Ni can also increase the solubility of Cr and Mo elements in the austenite matrix and improve the corrosion resistance of the alloy. At the same time, Ni itself also has good corrosion resistance.
[0021] Mo: In the laser cladding powder of the present invention, Mo is an element that resists local corrosion. The mechanism is that after local corrosion occurs, MoO4 in the solution 2- It will be adsorbed on the exposed metal substrate surface after the oxide film is broken, inhibiting the redissolution of the metal. However, too high Mo content will affect the mechanical properties and increase the cost, so the Mo content in the present invention is controlled at 2-5%.
[0022] Cu: In the laser cladding powder of the present invention, the addition of Cu can improve the corrosion resistance. However, too high a Cu content will significantly reduce the mechanical properties of the austenitic alloy, so the Cu content in the present invention is controlled at 0.5-3%, preferably 1-2.5%.
[0023] Al: In the laser cladding powder of the present invention, Al is a deoxidizer, which can reduce the content of oxide inclusions in the alloy. More importantly, the addition of a certain amount of Al element in the present invention can generate a Cr2O3+Al2O3 mixed oxide film on the alloy surface, thereby improving the material's anti-oxidation performance in high-temperature water vapor. However, too high an Al content will promote the formation of a ferrite phase, causing the material to present a dual-phase structure, which reduces the mechanical properties. Therefore, the Al element content in the present invention is controlled at 0.1-1.0%, and more preferably 0.3-0.8%.
[0024] Nb: In the laser cladding powder of the present invention, Nb is a strong carbide-forming element. In the alloy, Nb is more likely to combine with C than Cr to form finely dispersed NbC precipitates. These precipitates can not only strengthen the alloy, but also reduce the formation of Cr in the alloy. 23 C6 leads to the formation of chromium-depleted regions at the grain boundaries, thus improving the intergranular corrosion resistance of the alloy. However, too high a Nb content will cause a large amount of NbC to precipitate in the alloy, thus reducing the mechanical properties of the alloy. Therefore, the Nb content in the present invention is controlled at 0.01-0.1%, preferably 0.03-0.08%.
[0025] Furthermore, the laser cladding powder of the present invention is spherical, and its particle size is 25 to 200 μm.
[0026] In this embodiment, the laser cladding powder with a particle size of 25 to 200 μm can achieve better cladding quality and increase the process window of laser cladding.
[0027] Furthermore, in the laser cladding powder of the present invention, it also satisfies Ni eq ≥1.15×Cr eq -6.92; among them, Ni eq =Ni+30×C+0.5×Mn;Cr eq =Cr+Mo+1.5×Si+0.5×Nb, where each chemical element is substituted into the value before the percentage sign of its mass percentage.
[0028] In this embodiment, ensuring that the element content satisfies the above formula can improve the austenite stability of the material.
[0029] Furthermore, among the inevitable impurities in the laser cladding powder of the present invention, P≤0.03% and S≤0.03%.
[0030] Furthermore, among the inevitable impurities in the laser cladding powder of the present invention, P≤0.01% and S≤0.005%.
[0031] The inevitable impurities in the present invention are mainly P and S. P and S are both associated harmful impurity elements, which will reduce the thermoplasticity of the alloy and have an adverse effect on the hot working performance of the alloy. When the content of P and S elements reaches more than 0.03%, the corrosion resistance of the alloy will be seriously damaged. Therefore, in the present invention, the content of P and S elements is controlled below 0.03%, and more preferably P≤0.010% and S≤0.005%.
[0032] Furthermore, the uniform corrosion rate of the cladding layer prepared by using the laser cladding powder of the present invention in an oxygen corrosion environment with chloride ions and water is ≤0.01 mm / y.
[0033] Furthermore, the maximum pitting rate of the cladding layer prepared by using the laser cladding powder of the present invention in an oxygen corrosion environment with chloride ions and water is ≤0.1 mm / y.
[0034] Another object of the present invention is to provide a method for using laser cladding powder, which can be used to produce a metallurgical composite pipe with a cladding layer, thereby improving the oxygen corrosion resistance of the metallurgical composite pipe.
[0035] Based on the above invention objectives, the present invention also provides a method for using the laser cladding powder as described above, which includes the steps of: laser cladding the laser cladding powder under the protection of an inert gas to form a cladding layer on a substrate, and the laser spot used in the laser cladding process is a rectangular spot.
[0036] The laser cladding powder of the present invention has the following advantages and beneficial effects:
[0037] The laser cladding powder with high oxygen corrosion resistance for manufacturing metallurgical composite pipes of the present invention has excellent corrosion resistance in an oxygen corrosion environment accompanied by chloride ions and water. In some embodiments, the cladding layer prepared by using the laser cladding powder of the present invention has a uniform corrosion rate of ≤0.01 mm / y and a maximum pitting rate of ≤0.1 mm / y in an oxygen corrosion environment with chloride ions and water.
[0038] The laser cladding powder with high oxygen corrosion resistance for manufacturing metallurgical composite pipes described in the present invention can be used for laser cladding of inner and outer walls of steel pipes to improve the oxygen corrosion resistance of the pipes.
[0039] In some embodiments, the particle size of the laser cladding powder with high oxygen corrosion resistance for manufacturing metallurgical composite pipes described in the present invention is 25-200 μm, which can achieve better cladding quality and increase the process window of laser cladding. DETAILED DESCRIPTION
[0040] The laser cladding powder with high oxygen corrosion resistance for manufacturing metallurgical composite pipes and the method for using the same described in the present invention will be further explained and illustrated in conjunction with specific embodiments below. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.
[0041] In some embodiments, the laser cladding powders of Examples 1-6 and Comparative Examples 1-6 are prepared by vacuum smelting alloy, vacuum gas atomization powdering, and screening. The chemical composition content ratios of the laser cladding powders of each Example and Comparative Example are listed in Table 1.
[0042] Table 1. (wt%, the balance is Fe and other inevitable impurities except P and S)
[0043]
[0044]
[0045] Note: In Table 1, Ni eq =Ni+30×C+0.5×Mn;Cr eq =Cr+Mo+1.5×Si+0.5×Nb, where each chemical element is substituted into the value before the percentage sign of its mass percentage.
[0046] In each embodiment and comparative example, under the protection of inert gas, a laser cladding process is used to clad the laser cladding powder on the inner wall of a substrate tube with a length of 10 m and an outer diameter of 508 mm to form a cladding layer.
[0047] Among them, the laser spot used in the laser cladding process of each embodiment and comparative example is a rectangular spot, the rectangular laser spot size is 40×4mm, the laser power is selected as 12kW, the cladding line speed is 800mm / min, the overlap rate is 20%, and the powder feeding speed of the laser cladding powder is 150g / min.
[0048] Table 2 lists the manufacturing process parameters of the large-diameter laser cladding metallurgical composite tubes of Examples 1-6 and the comparative tubes of Comparative Examples 1-4.
[0049] Table 2.
[0050]
[0051]
[0052] The cladding layers obtained after the above process were tested, and the cladding time and cladding quality of each embodiment and comparative example are listed in Table 3.
[0053] Table 3.
[0054]
[0055] As can be seen from Table 3, the quality of the cladding layer obtained by laser cladding using the laser cladding powder of the present invention is good. Since the powder particle size of Examples 1-6 and Comparative Examples 1-4 is in the range of 25 to 200 μm, the cladding quality is good. However, the powder particle size of Comparative Example 5 is too small, and the fluidity is poor, resulting in uneven powder feeding or powder blockage in the powder feeder, poor cladding stability, large fluctuations in the thickness of the cladding layer, and poor cladding quality. The powder particle size of Comparative Example 6 is too large, and the light absorption area of the powder per unit weight is small, resulting in part of the powder not being completely melted, and the cladding layer has obvious defects.
[0056] Combining Table 2 and Table 3, it can be seen that as the particle size of laser cladding powder increases, the cladding time will increase.
[0057] In addition, in order to verify the oxygen corrosion resistance of the present invention in an oxygen corrosion environment with chloride ions and water, the salt cave compressed air energy storage working condition was simulated to evaluate the oxygen corrosion resistance of each embodiment and comparative example, and the results are listed in Table 4.
[0058] The corrosive medium is 230g / L NaCl solution (i.e. saturated NaCl solution), the compressed air (with an oxygen content of 21%) has a pressure of 12MPa, a temperature of 70°C, and a compressed air flow rate of 1.5m / s. According to "ASTM G111-21 Standard Guide for Corrosion Tests in High Temperature or High Pressure Environment, or Both" and "JB / T 7901-1999 Metal Materials Laboratory Uniform Corrosion Full Immersion Test Method", the average corrosion rate of the sample is tested and the presence of pitting is observed under a stereo microscope. Examples 1-6 and Comparative Examples 1-4 cut full-wall thickness pipe bodies, seal the exposed base pipes with epoxy resin, expose the cladding layer, and only calculate and observe the cladding layer information. Comparative Examples 5-6 were not tested for oxygen corrosion resistance due to poor cladding quality.
[0059] Table 4.
[0060]
[0061] It can be seen from Table 4 that the cladding layers obtained by the laser cladding powders of various embodiments of the present invention have a uniform corrosion rate of ≤0.008 mm / y and a maximum pitting rate of ≤0.09 mm / y in an oxygen corrosion environment with chloride ions and water. However, since the chemical element content of Comparative Examples 1-4 does not meet the requirements of the present invention, the uniform corrosion rate and the maximum pitting rate are higher than those of the embodiments of the present invention.
[0062] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.
[0063] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.
Claims
1. A laser cladding powder with high oxygen corrosion resistance, containing Fe and inevitable impurities, characterized in that: It also contains the following chemical elements in percentage by mass: 0<C≤0.03%, Cr: 15~35%, Ni: 30~60%, Mo: 2~5%, Cu: 0.5~3%, Al: 0.1~1.0%, Nb: 0.01~0.1%.
2. The laser cladding powder according to claim 1, characterized in that: The mass percentage of each chemical element is: 0<C≤0.03%, Cr: 15~35%, Ni: 30~60%, Mo: 2~5%, Cu: 0.5~3%, Al: 0.1~1.0%, Nb: 0.01~0.1%, and the balance is Fe and inevitable impurities.
3. The laser cladding powder according to claim 1 or 2, characterized in that: Its particle size is 25 to 200 μm.
4. The laser cladding powder according to claim 1 or 2, characterized in that: The mass percentage of each chemical element satisfies at least one of the following: 0<C≤0.02%; Cr:19~30%; Cu: 1-2.5%; Al:0.3~0.8%; Nb: 0.03~0.08%.
5. The laser cladding powder according to claim 1 or 2, characterized in that: It also satisfies Ni eq ≥1.15×Cr eq -6.92; among them, Ni eq =Ni+30×C+0.5×Mn;Cr eq =Cr+Mo+1.5×Si+0.5×Nb, where each chemical element is substituted into the value before the percentage sign of its mass percentage.
6. The laser cladding powder according to claim 1 or 2, characterized in that: Among the inevitable impurities, P ≤ 0.03% and S ≤ 0.03%.
7. The laser cladding powder according to claim 6, characterized in that: Among the inevitable impurities, P ≤ 0.01% and S ≤ 0.005%.
8. The laser cladding powder according to claim 1 or 2, characterized in that: The uniform corrosion rate of the cladding layer prepared therefrom in an oxygen corrosion environment containing chloride ions and water is ≤0.01 mm / y.
9. The laser cladding powder according to claim 1 or 2, characterized in that: The maximum pitting rate of the cladding layer prepared therefrom in an oxygen corrosion environment with chloride ions and water is ≤0.1 mm / y.
10. The method for using the laser cladding powder according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: performing laser cladding on the laser cladding powder under the protection of an inert gas to form a cladding layer on a substrate; wherein the laser spot used in the laser cladding process is a rectangular spot.
Citation Information
Patent Citations
Iron-based alloy powder for high strength and toughness laser deposited coating
CN101974724A
Anti-corrosion laser cladding powder and cladding method and application thereof
CN108326287A